Influence of local anesthetics with or without epinephrine 1/80000 on blood pressure and heart rate: A randomized double-blind experimental clinical trial - Mohammad Ketabi; Mehrnaz Sadighi Shamami; Maryam Alaie; Mehrnoosh Sadighi Shamami (Wolters Kluwer Medknow Publications, 2012)
Background: Local anesthesia (LA) with epinephrine have an important role in pain and bleeding control. However, most clinicians believe LA + epinephrine may cause rapid raise in blood pressure (BP) and heart rate (HR). The aim of this research was to compare the changes in HR and BP after administration of lidocaine with and without epinephrine 1/80000 in two infiltration (INF) and inferior alveolar nerve block methods (IANB). Materials and Methods: The study was a randomized double-blind experimental clinical trial. Forty subjects were divided into two equal groups and two subgroups. In one group, INF and in the other group, IANB were used and, further, in one subgroup lidocaine and in another subgroup, lidocaine plus epinephrine were used. BP and HR were recorded before and 10 min after. The paired t-test for intragroup differences and independent t-test for intergroup analysis were used at the significant level of P ≤0.05. Results: The mean BP and HR values were reduced after injection of lidocaine in both INF and IANB compared with baseline. The differences were statistically significant (P < 0.05), but, on comparing these values between the two injection methods, the differences were not statically significant (P = 0.089 and 0.066, respectively). The mean BP and HR values were increased after injection of lidocaine plus epinephrine in both INF and IANB compared with baseline, and these were statistically significant (P < 0.05) but, on comparing these values between the two methods, the differences were not statically significant (P = 0.071 and 0.092, respectively). Conclusion: The rise in BP and HR following injection of lidocaine plus epinephrine was statistically significant compared with baseline in both INF and IANB, but this was not clinically and numerically considerable.